Digital Financial Management of MSMEs: The Impact of Financial Literacy and Financial Technology - Irna Triannur Lubis; Ningsi, Etty Harya; Manurung, Lambok; Widodo, Slamet (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
Financial management is important for everyone, including MSMEs. In order to avoid financial problems, MSMEs must have good financial management skills. This research aims to test financial literacy and fintech in financial management and lifestyle to moderate the relationship between these three variables. This study uses a quantitative approach. The number of samples used was 125 using purposive sampling technique. The data collection technique uses questionnaires. This research uses the Partial Least Square method with SmartPLS 4 software as material for analyzing research data. The findings of this research show that financial literacy and fintech have a positive and significant effect on financial management. MSMEs that have a good understanding of financial literacy will be able to manage their finances by paying their obligations on time, knowing the types and products of insurance, understanding the world of investment, and having a good understanding of the basics of financial literacy. This will also get better. The convenience provided by fintech minimizes risk and allows users to benefit from financial management in both saving and investment activities. Lifestyle has no effect on moderating the relationship between financial literacy and fintech. This is possible because there is a gender gap among respondents.